siRNA targeting Schlemm's canal endothelial tight junctions enhances outflow facility and reduces IOP in a steroid-induced OHT rodent model - Farrar, Gwyneth; Campbell, Matthew; Humphries, Peter; Humphries, Marian (My University, 2021)
Systemic or localized application of glucocorticoids (GCs) can lead to iatrogenic ocular hypertension, which is a leading cause of secondary open-angle glaucoma and visual impair ment. Previous work has shown that dexamethasone increases zonula occludens-1 (ZO-1) protein expression in trabecular meshwork (TM) cells, and that an antisense oligonucleotide inhibitor of ZO-1 can abolish the dexamethasone-induced in crease in trans-endothelial flow resistance in cultured Schlemm’s canal (SC) endothelial and TM cells. We have pre viously shown that intracameral inoculation of small inter fering RNA (siRNA) targeting SC endothelial cell tight junc tion components, ZO-1 and tricellulin, increases aqueous humor outflow facility ex vivo in normotensive mice by reversibly opening SC endothelial paracellular pores. In this study, we show that targeted siRNA downregulation of these SC endothelial tight junctions reduces intraocular pressure (IOP) in vivo, with a concomitant increase in conventional outflow facility in a well-characterized chronic steroid induced mouse model of ocular hypertension, thus represent ing a potential focused clinical application for this therapy in a sight-threatening scenario.
Keywords: glucocorticoids (GCs); intraocular pressure;; Schlemm's canal; Trabecular meshwork; Tight junctions; Primary open angle glaucoma; Pores; Outflow facility; Ocular hypertension; Intracameral; Schlemm’s canal